OPTIMATION OF RHENIUM-OXO-GLUCONATE SYNTHESIS AS A PRECURSOR FOR SYNTHESISOF RHENIUM(V)-TETROFOSMIN - Widyastuti Widyastuti; A. H. Gunawan; Sriyono Sriyono (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
OPTIMATION OF RHENIUM-OXO-GLUCONATE SYNTHESIS AS A PRECURSOR FOR SYNTHESISOF RHENIUM(V)-TETROFOSMIN. Rhenium-188 or Rhenium-186 labeled compounds have been widely used as therapeutic radiopharmaceutical for cancer. Most of rhenium (Re) radiopharmaceuticals involve Re with oxidation state of 5, one of which is Re-dioxo-tetrofosmin. Complexes of Re(V)-ligand can be generated fromRe(V)-oxo-gluconate through ligand exchange process. Optimation of rhenium-oxo-gluconate synthesis was carried out by varying mole ratio of gluconate to perrhenate and reaction time, in which 188Re was added to perrhenate solution as radiotracer. Stability study of Re-oxo-gluconate at room temperature and elevating temperature was carried out bymeasuring its radiochemical puritywithin several hours. Radiochemical purity was analysed using 2 systems of paper chromatography with Whatman-3 paper as solid phase, and acetone and saline as mobile phases, respectively. Highest yield was obtained using mole ratio of 6000, i.e 87.43% (SD=3.01%), and the optimum reaction time was 1 hour. Storage at room temperature and elevating temperature resulted in the decrease of radiochemical purity of 10% (within 3 hrs) and 30% (within 1 hour), respectively. Re-dioxo-tetrofosmin which was used as a model of Re(V)-ligand, was obtained through ligand exchange reaction with the yield of 92.1%. The result showed that Re-oxo-gluconate can be successfully synthesized in high yield but low stability.